COMPARISON OF MODERATE-TO-VIGOROUS PHYSICAL ACTIVITY LEVELS BETWEEN PHYSICAL EDUCATION, SCHOOL RECESS AND AFTER-SCHOOL TIME IN SECONDARY SCHOOL STUDENTS: AN ACCELEROMETER-BASED STUDY - Mayorga Vega, Daniel; Parra Saldías, Maribel; Viciana, Jesús (Kinesiology, 2017)
Regular physical activity is an important factor of health in youth. Unfortunately, in Chile 85% of adolescents do not achieve the 60 min daily recommendation of moderate-to-vigorous physical activity. Physical education, school recess and after-school time are considered crucial environments for adolescents to meet the recommended moderate-to-vigorous physical activity levels. This study compared the moderateto-vigorous physical activity levels between physical education, school recess and after-school time in Chilean secondary school students, and examined the influence of gender and weight status. A hundred and fifty-six Chilean secondary school students (finally 89 participants were included), aged 13-14 years, were monitored by objective measures of moderate-to-vigorous physical activity during physical education, school recess and after-school time. Results indicated statistically significant differences in moderate-to-vigorous physical activity between contexts (total minutes: After-school time>physical education>school recess; percentage: Physical education>after-school time=school recess, p<.001) as well as a gender-related influence (boys>girls, p<.05). Policy-makers are encouraged to increase the number of physical education classes and teachers to ensure that more physical education class time is spent in moderate-to-vigorous physical activity, especially among girls. The increase in students’ moderate-to-vigorous physical activity levels during school recess and after-school time should also be promoted. Key words: accelerometry, exercise, healthy behavior, public health, adolescence, youth